Dante's Purgatorio : the Vision of Purgatory from The Divine Comedy. - Alighieri, Dante (First Avenue classics., 2015)
Purgatorio is the second part of Italian poet Dante Alighieri's epic poem Divine Comedy and describes Dante's climb up the Mount of Purgatory. Dante visits the seven terraces of Purgatory, where sinners are cleansing themselves in preparation for entering Paradise.